2022
DOI: 10.1136/pn-2022-003574
|View full text |Cite
|
Sign up to set email alerts
|

Muscle cramps and contractures: causes and treatment

Abstract: Muscle cramps are painful, sudden, involuntary muscle contractions that are generally self-limiting. They are often part of the spectrum of normal human physiology and can be associated with a wide range of acquired and inherited causes. Cramps are only infrequently due to progressive systemic or neuromuscular diseases. Contractures can mimic cramps and are defined as shortenings of the muscle resulting in an inability of the muscle to relax normally, and are generally myogenic. General practitioners and neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…We demonstrated that older age (equal to or more than 66 years) was the only factor associated with muscle cramps in patients with liver diseases. This prevalence may be smaller, as 37% of healthy people per year have muscle cramps as part of the spectrum of normal human physiology [ 15 ], although food and nutrition may affect the status of muscle cramps [ 16 ]. In this study, however, we observed that 67% of patients with muscle cramps had not yet received appropriate therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrated that older age (equal to or more than 66 years) was the only factor associated with muscle cramps in patients with liver diseases. This prevalence may be smaller, as 37% of healthy people per year have muscle cramps as part of the spectrum of normal human physiology [ 15 ], although food and nutrition may affect the status of muscle cramps [ 16 ]. In this study, however, we observed that 67% of patients with muscle cramps had not yet received appropriate therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…Motor neuron disease, spinobulbar muscular atrophy, spinal muscular atrophy, radiculopathy, motor, and sensory peripheral neuropathies, peripheral nerve hyperexcitability, and neuromyotonia are neurogenic causes of symptomatic muscle cramps. Electrolyte imbalance, hepatic and renal dysfunction, vitamin deficiency, diabetes mellitus, (para)thyroid dysfunction, and chronic venous insufficiency, are non-neuromuscular causes of symptomatic muscle cramps [ 15 ]. If muscle cramps are observed in patients with liver diseases, we should rule out the diseases above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation